The Issue of Attribution of Acts Committed in the Information Space - I. G. Lukiyantseva (Московский журнал международного права, 2025)
INTRODUCTION. Due to the recent trend related to the use of information and communication technologies by certain states with the aim to assert their geopolitical superiority, study of the issue of attribution of responsibility for acts committed in the information space as well as possible of responses to such attacks becomes even more relevant. Therefore, in the article the problems related to international responsibility, particularities of attacks in information space and ways to attribute such attacks, as well as effectiveness of international law are analyzed.MATERIALS AND METHODS. The research examines treaties, international customs, general widely recognized principles of international law, as well as resolutions, materials and documents of specialized working groups, and doctrine. General scientific and specific scientific methods of enquiry (methods of analysis and synthesis, deduction, induction, dialectical and formal legal methods) were used in the preparation of the study.RESEARCH RESULTS. The result of the conducted research is the conclusion that it is impossible to effectively regulate issues arising from the issue of attribution of acts committed in the information space exclusively with the current international law. Therefore, there is a need to develop a relevant international treaty taking into account the provisions of the concept of the UN Convention on International Information Security. At the same time, in order to effectively attribute an act, it is important to take into account the political, technical and legal elements of attribution of responsibility.DISCUSSION AND CONCLUSIONS. The article considers approaches to the issue of attribution of attacks in the information space as well as of possible ways of responding to such attacks within the framework of current international law. The problem of possible application of international humanitarian law, especially issue of interpretation of “attack” for the purposes of attacks in information space was also examined. In addition, the author analyzes the provisions of the concept of the UN Convention on International Information Security.The author concludes that current international law is not sufficient for effective attribution of an act committed in the information space. Elaboration of additional international legal regulation that would take into account the particularities of the information space is required. It is also crucial to develop international cooperation in this area, including through the creation of a global register of contact points.